The PCR Procedure to Detect Rapidly Two Common Bacterial Causing Pneumonia in Air Enviroment - Tran Thi Huyen, Nga (VNU Journal of Science: Earth and Environmental Sciences; Vol 33 No 1S, 2017)
In the environment, there are many bacteria, which can spread in the air, causing serious diseases like pneumonia, respiratory infections. Nowadays, culture is used as a traditional method for detecting and identifying bacteria. Although this method has highly sensitive, but it takes a long time to get results (24-48 hours). Therefore, the development of a rapid detection method and meanings to control air quality is essential. This study is designed to develop a procedure for the detection of bacterial causing pneumonia in the air with high specificity based on multiplex PCR. Acinetobacter baumannii and Pseudomonas aeruginosa were selected as research targets because they are two of the most dangerous bacteria, according to WHO.